2010
DOI: 10.1016/j.biomaterials.2009.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Biological performance of mussel-inspired adhesive in extrahepatic islet transplantation

Abstract: There is significant need for effective medical adhesives that function reliably on wet tissue surfaces with minimal inflammatory insult. To address these performance characteristics, we have generated a synthetic adhesive biomaterial inspired by the protein glues of marine mussels. In-vivo performance was interrogated in a murine model of extrahepatic syngeneic islet transplantation, as an alternative to standard portal administration. The adhesive precursor polymer consisted of a branched poly(ethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
258
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(263 citation statements)
references
References 38 publications
4
258
0
1
Order By: Relevance
“…The structural and mechanical lessons gained by investigating the byssus network could provide us with important design principles that can be applied in the fabrication of interfacial materials that can function effectively under dynamic loadings, such as attachments to ships, submarines, in wind turbines, or for applications in space technologies 4,25,26 . From a slightly different perspective, we have found that the use of about 20% soft material in mussel threads is crucial in light of impact absorption and force reduction for the entire animal.…”
Section: Discussionmentioning
confidence: 99%
“…The structural and mechanical lessons gained by investigating the byssus network could provide us with important design principles that can be applied in the fabrication of interfacial materials that can function effectively under dynamic loadings, such as attachments to ships, submarines, in wind turbines, or for applications in space technologies 4,25,26 . From a slightly different perspective, we have found that the use of about 20% soft material in mussel threads is crucial in light of impact absorption and force reduction for the entire animal.…”
Section: Discussionmentioning
confidence: 99%
“…The extraordinary ability of the byssus to bind to a variety of pristine and bio-fouled surfaces (e.g. glass, metal, plastic) in a matter of minutes while immersed in the high salt and basic pH conditions imposed by seawater has attracted the attention of many researchers and resulted in the creation of biomimetic glues for medical and broader use [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In this figure, catechol, [22] dopamine [23] or dopa [24] was coupled to polymer chains ends or as side chains of polymerizable catechol monomers with the linear or branched polymer backbone, which are commonly made of polystyrene, [25] poly(ethylene glycol), [26] poly-(acrylate/methacrylate), [27] or poly(acrylamide/methacrylamide) [28] ( Figure 3). It is demonstrated that both of catechols and cations have a classic synergy for underwater adhesion.…”
Section: Molecular Design Principle Of Musselinspired Polymeric Undermentioning
confidence: 99%
“…[51] Based on the mussels protein, a mimetic biological adhesive was fabricated with a branched poly(ethylene glycol) (PEG) with catechol end groups ( Figure 9A). [22] After adding sodium periodate solution to induce gelation, the branched catechol-functional PEG (cPEG) solutions form hydrogels in less than 1 min ( Figure 9B). Subsequently, the cPEG adhesive elicited minimal acute or chronic inflammatory response in C57BL6 mice, and maintained an intact interface with supporting tissue up to one year.…”
Section: Biological Adhesives Of Catechol-functional Polymermentioning
confidence: 99%